1999
DOI: 10.1111/j.1750-3639.1999.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alterations in Alzheimer's Disease

Abstract: There is increasing evidence that free radical damage to brain lipids, carbohydrates, proteins, and DNA is involved in neuron death in neurodegenerative disorders. The largest number of studies have been performed in Alzheimer's disease (AD) where there is considerable support for the oxidative stress hypothesis in the pathogenesis of neuron degeneration. In autopsied brain there is an increase in lipid peroxidation, a decline in polyunsaturated fatty acids (PUFA) and an increase in 4‐hydroxynonenal (HNE), a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
375
0
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 720 publications
(385 citation statements)
references
References 124 publications
5
375
0
5
Order By: Relevance
“…The healthy brain is protected from oxidative injury by antioxidant defences that include antioxidant enzymes and free radical scavengers. Many recent investigations have strengthened the hypothesis that an impairment in cellular total antioxidant capacity (TAC) plays a central role in AD [47,46]. Recently, we have found that lymphoblasts and fibroblasts carrying APP and PS-1 gene mutations have a significant TAC impairment compared to healthy controls [15].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The healthy brain is protected from oxidative injury by antioxidant defences that include antioxidant enzymes and free radical scavengers. Many recent investigations have strengthened the hypothesis that an impairment in cellular total antioxidant capacity (TAC) plays a central role in AD [47,46]. Recently, we have found that lymphoblasts and fibroblasts carrying APP and PS-1 gene mutations have a significant TAC impairment compared to healthy controls [15].…”
Section: Introductionmentioning
confidence: 88%
“…Mitochondria are the major subcellular source of superoxide anion radical, which can interact with nitric oxide (NO) to form peroxynitrite [12,71]. ROS and peroxynitrite accumulation results in damage to major macromolecules in cells, including lipids, proteins and nucleic acids [47,60,62,68]. The lipoperoxidation process could influence the pathogenesis of AD [55,59].…”
Section: Introductionmentioning
confidence: 99%
“…90 Although in TBI-related studies, 4-HNE levels were evaluated in brain tissue, studies examining this compound in CSF and plasma have been carried out for other neurologic disorders such as Alzheimer's disease, amyotrophic lateral sclerosis, and stroke. [91][92][93] …”
Section: -Hydroxynonenalmentioning
confidence: 99%
“…Free radical reactions and oxidative stress [28,29], as well as unregulated immune response [30,31], are believed to be key factors for the pathogenesis of AD, whereas recent reports suggested a link between heart disease, hypercholesterolemia, and…”
mentioning
confidence: 99%
“…Free radical reactions and oxidative stress [28,29], as well as unregulated immune response [30,31], are believed to be key factors for the pathogenesis of AD, whereas recent reports suggested a link between heart disease, hypercholesterolemia, and AD [32,33]. Thus, the well-documented antioxidant, anti-inflammatory, and antiatherogenic properties of OE may offer a multistage approach against the diverse mechanisms, which are inherent to AD.…”
mentioning
confidence: 99%